Imaging protocols for CT chest: A recommendation - Bhalla, Ashu Seith; Das, Abanti; Naranje, Priyanka; Irodi, Aparna; Raj, Vimal; Goyal, Ankur (Indian Journal of Radiology and Imaging, 2019)
Computed Tomography (CT) is the mainstay of diagnostic imaging evaluation of thoracic disorders. However, there are a number of CT protocols ranging from a simple non-contrast CT at one end of the spectrum, and CT perfusion as a complex protocol available only on high-end scanners.With the growing diversity, there is a pressing need for radiologists, and clinicians to have a basic understanding of the recommended CT examinations for individual indications. This brief review aims to summarise the currently prevalent CT examination protocols, including their recommended indications, as well as technical specifications for performing them.
Keywords: Computed tomography angiography; computed tomography chest; computed tomography contrast; dual energy computed tomography; low-dose computed tomography; protocol; pulmonary embolism